Customer service for hospitality and tourism - Hudson, Louise; Hudson, Simon (Woodeaton, Oxford Goodfellow, 2013)
Chapters cover important topics such as the financial and behavioural consequences of customer service, consumer trends influencing service, developing and maintaining a service culture, managing service encounters, the importance of market research, building and maintaining customer relationships, providing customer service through the servicescape, the impact of technology on customer service, the importance of service recovery, and promoting customer service internally and externally.
Keywords: Quản trị DV Du lịch và Lữ hành